L’épaisseur et l’ambivalence des expériences urbaines quotidiennes - Fanny Vuaillat (Société Royale Belge de Géographie and the Belgian National Committee of Geography, 2021)
What children experience in the city continues to elude understanding of everyday life and urban dynamics. After spending time with pupils from a secondary school in Echirolles (France), located in a deprived and stigmatised neighbourhood, this article discusses their everyday urban experiences. They are thought of as thick with three thematic registers: a discourse of situation or positioning in time and space, sensitive attentions and the emotional register, dominated here by fear and anger. The experiences are also ambivalent, combining opposites: child and young, here and far away, discomfort and pleasure, suffering and acting, memory and immediacy. Understanding the thickness and ambivalence of experiences helps to avoid the risk of a homogenous view of urban childhood.